(untitled) - O'Hair, Dan (Boston, 2019)
The Sixth Edition is filled with new examples, research, handy tools, and digital support to help students master the basics of public speaking in the classroom and beyond. New speeches and examples from people like Will Ferrell, Emma Watson, and students from Marjory Stoneman Douglas High School engage students in current issues, demonstrate the impact of speech, and provide successful models. Practical advice on topics like how to determine which organizational pattern to use when, how to adapt to an audience, and how to incorporate inclusive language provide easy-to-apply guidance.
Kỹ năng giao tiếp và thuyết trình chuyên nghiệp
Keywords: Nói trước công chúng,Public speaking